The need for supplemental blocks in single versus triple injections in infraclavicular brachial plexus blocks with a medial approach: a clinical and anatomic study - Hande G. Aytuluk; Tuncay Colak (Revista Brasileira de Anestesiologia, 2020)
Abstract Background and objectives: To evaluate the single-injection and triple-injection techniques in infraclavicular blocks with an ultrasound-guided medial approach in terms of block success and the need for supplementary blocks. Methods: This study comprised 139 patients who were scheduled for elective or emergency upper-limb surgery. Patients who received an infraclavicular blocks with a triple-injection technique were included in Group T (n = 68). Patients who received an infraclavicular blocks with a single-injection technique were included in Group S (n = 71). The number of patients who required supplementary blocks or had complete failure, the recovery time of sensory blocks and early and late complications were noted. Results: The block success rate was 84.5% in Group S, and 94.1% in Group T without any need for supplementary nerve blocks. The blocks were supplemented with distal peripheral nerve blocks in 8 patients in Group S and in 3 patients in Group T. Following supplementation, the block success rate was 95.8% in Group S and 98.5% in Group T. These results were not statistically significant. A septum preventing the proper distribution of local anesthetic was clearly visualized in 4 patients. The discomfort rate during the block was significantly higher in Group T (p < 0.05). Conclusion: In ultrasound-guided medial-approach infraclavicular blocks, single-injection and triple-injection techniques did not differ in terms of block success rates. The need for supplementary blocks was higher in single injections than with triple injections. The presence of a fascial layer could be the reason for improper distribution of local anesthetics around the cords.